Development an Interactive Physics Learning Based on Google Sites Integrated with Local Wisdom - Isabel Coryunitha Panis; Egidius Dewa; Oktavianus Ama Ki’i (Jurnal Penelitian Pendidikan IPA, 2026)
The limited availability of interactive physics learning media that meaningfully integrate local wisdom remains a challenge in contextual science instruction. This study aimed to develop a Google Sites–based interactive physics learning design integrated with the local wisdom of the Manggarai gong and to determine its feasibility for classroom use. The study employed a Research and Development approach using a modified Borg and Gall model, covering needs analysis, initial product design, expert validation, and revision. The product was designed with a structured learning sequence consisting of contextual orientation, pretest, learning objectives, sound wave materials, virtual simulations, ethnoscience-based cultural integration, posttest, and student reflection. Data were analyzed using Aiken’s V to assess content validity across material and media aspects. The results showed that all validation indicators achieved Aiken’s V values ranging from 0.83 to 1.00, exceeding the acceptable validity threshold of 0.80. These findings indicate strong expert agreement on content relevance, conceptual accuracy, media quality, and the appropriateness of integrating local wisdom into physics learning. In conclusion, the developed learning design is content-valid and feasible for use, with minor revisions required before practicality and effectiveness testing